PENGARUH PENGETAHUAN TENTANG HUKUM LINGKUNGAN DAN PENILAIAN ATAS REGULASI PEMERINTAH TERHADAP PARTISIPASI PELAKU INDUSTRI DALAM MENGELOLA KAWASAN INDUSTRI DI KOTA SINGKAWANG - Hassim, Rudi Agustian (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
The objective of this research is to analyze the effects of knowledge about environmental law and assessment of government regulations on industrial doers’ participation in managing the industrial area in Singkawang city. The sample of this research were 48 persons which randomly taken. The data were analyzed by using ANAVA 2 X 2. Findings of the research indicated that the industrial doers who were knowledgeable about environmental law and had positive assessment of government regulations participated better in industrial management than those who had negative assessment. Therefore, the two variables should be taken into consideration to increase the doers’ participation in managing industrial area.